ONLINE NON-CASH GOLD PURCHASE AND SALE TRANSACTIONS THROUGH THE SHOPEE PLATFORM FROM THE PERSPECTIVE OF ISLAMIC COMMERCE - Tiara Oktavina; Mumtazinur; Muhammad Husnul (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2026)
This article discusses cashless online gold transactions on the Shopee platform amid ongoing conflicts with Sharia economic law. The purpose of this study is to determine and analyse how cashless online gold transactions on the Shopee platform are conducted, and to examine their perspective on Islamic law. This research method is qualitative and uses a conceptual approach; it is normative legal research. The results and discussion in this article indicate that digital gold transactions on Shopee do not fully comply with Sharia principles due to the unclear mechanism of the sale and purchase agreement in accordance with Sharia economic law, the absence of direct handover, and the potential for elements of gharar and usury in the buying and selling process. Therefore, supervision, consumer education, and adjustments to transaction mechanisms are needed to comply with Islamic law, so that digital gold investment can become a halal, safe, and trusted financial instrument for Muslims.